Experimental assessment of the CO2 phytoremediation efficiency of living walls in indoor environments - Gianluca Coccia; Feliciano Falcone; Luca Tarabelli; Costanzo Di Perna; Elisa Di Giuseppe; Marco D’Orazio (Building and Environment, 2026)

Floods connect tropical river–floodplain food webs but shrink fish community isotopic trophic niches - Colton N. Perna; Luke McPhan; Timothey D. Jardine; Lauren Meyer; R. Keller Kopf (Hydrobiologia, 2026)
Lateral connectivity between the floodplain and river channel is hypothesised to expand fish community isotopic trophic niches and increase overlap of river–floodplain food webs. To evaluate how flood magnitude influences trophic dynamics in a large tropical free-flowing river (Roper River, Australia), we measured community isotopic niches in low- and high-magnitude flood years in wetland and river habitats. Contrary to our hypothesis, isotopic niche area of the river fish community contracted following the high-magnitude flood year, when compared to a low-magnitude flood year. Wetland fishes maintained more similar niche space regardless of flood conditions, but showed the same pattern of contracting niche area following a large magnitude flood. Niche overlap was lowest for river low-magnitude flood and wetland high-magnitude flood and highest for river and wetland high-magnitude flood. Our results suggest that river–floodplain fish communities exploit a wider isotopic range of food sources during low-flood years, including enriched sources of potentially marine origin, while sharing abundant less diverse resources in high-magnitude flood years. As water resources in tropical rivers are developed, our findings highlight the importance of conserving multiple dimensions of connectivity in riverine landscapes to maintain intact river–floodplain food webs.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Lithologies of Dimorphos revealed by boulder morphological classes - F. Tusberti; M. Pajola; L. Penasa; A. Lucchetti; M. Massironi; G. Munaretto; J. Beccarelli; R. Pozzobon; C. Rossi; G. Poggiali; N. Murdoch; C.Q. Robin; et al. (Icarus, 2025)

Low impact methods for microbial lipids production for third generation biofuels and biobased polyurethanes - Antonio Caporusso; Michele Casiello; Vincenzo De Leo; Antonio Perna; Lucia Catucci; Lucia D’Accolti; Angela Capece; Isabella De Bari (Journal of Environmental Chemical Engineering, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Liver-on-chip model and application in predictive genotoxicity and mutagenicity of drugs - B. Kopp; A. Khawam; K. Di Perna; D. Lenart; M. Vinette; R. Silva; T.B. Zanoni; C. Rore; G. Guenigault; E. Richardson; T. Kostrzewski; A. Boswell; et al. (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2024)

Evaluation of effectiveness and resources consumption of water mist spray systems in Mediterranean areas by predictions based on LSTM Recurrent Neural Networks - Marco D'Orazio; Costanzo Di Perna; Elisa Di Giuseppe; Gianluca Coccia; Serena Summa (Sustainable Cities and Society, 2023)

Experimental evaluation of a water spray system for semi-outdoor spaces: Analysis of the effect of the operational parameters - Gianluca Coccia; Serena Summa; Elisa Di Giuseppe; Marco D’Orazio; Michele Zinzi; Costanzo Di Perna (Building and Environment, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Impact of HIV infection on sustained virological response to treatment against hepatitis C virus with pegylated interferon plus ribavirin - P. Monje-Agudo; A. Castro-Iglesias; A. Rivero-Juárez; F. Martínez-Marcos; E. Ortega-González; L. M. Real; B. Pernas; N. Merchante; P. Cid; J. Macías; M. D. Merino; A. Rivero; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Root hairs: development, growth and evolution at the plant-soil interface - Sourav Datta; Chul Min Kim; Monica Pernas; Nuno D. Pires; Hélène Proust; Thomas Tam; Priya Vijayakumar; Liam Dolan (Plant and Soil, 2011)

Annotation and overview of the Pseudomonas savastanoi pv. savastanoi NCPPB 3335 draft genome reveals the virulence gene complement of a tumour‐inducing pathogen of woody hosts - Pablo Rodríguez‐Palenzuela; Isabel M. Matas; Jesús Murillo; Emilia López‐Solanilla; Leire Bardaji; Isabel Pérez‐Martínez; Martín E. Rodríguez‐Moskera; Ramón Penyalver; Maria M. López; José M. Quesada; Bryan S. Biehl; Nicole T. Perna; et al. (Environmental Microbiology, 2010)
Summary Pseudomonas savastanoi pv. savastanoi is a tumour‐inducing pathogen of Olea europaea L. causing olive knot disease. Bioinformatic analysis of the draft genome sequence of strain NCPPB 3335, which encodes 5232 predicted coding genes on a total length of 5856 998 bp and a 57.12% G + C, revealed a large degree of conservation with Pseudomonas syringae pv. phaseolicola 1448A and P. syringae pv. tabaci 11528. However, NCPPB 3335 contains twelve variable genomic regions, which are absent in all previously sequenced P. syringae strains. Various features that could contribute to the ability of this strain to survive in a woody host were identified, including broad catabolic and transport capabilities for degrading plant‐derived aromatic compounds, the duplication of sequences related to the biosynthesis of the phytohormone indoleacetic acid ( iaaM, iaaH ) and its amino acid conjugate indoleacetic acid‐lysine ( iaaL gene), and the repertoire of strain‐specific putative type III secretion system effectors. Access to this seventh genome sequence belonging to the ‘ P. syringae complex’ allowed us to identify 73 predicted coding genes that are NCPPB 3335‐specific. Results shown here provide the basis for detailed functional analysis of a tumour‐inducing pathogen of woody hosts and for the study of specific adaptations of a P. savastanoi pathovar.

Performance of two commercial blood IFN-γ release assays for the detection of Mycobacterium tuberculosis infection in patient candidates for anti-TNF-α treatment - M. Bocchino; A. Matarese; B. Bellofiore; P. Giacomelli; G. Santoro; N. Balato; F. Castiglione; R. Scarpa; F. Perna; G. Signoriello; D. Galati; A. Ponticiello; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Nicotine sensitization in adult male and female rats quinpirole-primed as neonates - Marla K. Perna; Zackary A. Cope; Amanda M. Maple; Ian D. Longacre; Jennifer A. Correll; Russell W. Brown (Psychopharmacology, 2008)

Mast cell inhibition and reduced ventricular arrhythmias in a swine model of acute myocardial infarction upon therapeutic administration of relaxin - S. Nistri; L. Cinci; A.-M. Perna; E. Masini; D. Bani (Inflammation Research, 2008)

Isotopic Model (NISOTOP) used to Investigate 15N-Urea Transformations in the Presence of Phenanthrene, Chrysene and Benzo(a)pyrene in a Soil–Plant System - S. Cervelli; F. Di Giovanni; C. Perna; D. Perret (Water, Air, & Soil Pollution, 2000)